Analysis of The Influence of Product Design, Product Quality and Competitive Prices on Purchasing Decisions Through Brand Image (Study on Pekanbaru Sleepwalking Customers) - Thomas, Jody Derwin; Restuti, Sri; Musfar, Tengku Firli (Westscience Press, 2024)
This study aims to determine the influence of product design, product quality and competitive prices on purchasing decisions through brand image (Study on Pekanbaru Sleepwalking Customers). The population in this study is all the customers of Sleepwalking who have visited more than 2 times, whose age 10 and over also has the intensity of visiting at least 1 time during the past year. Primary data was collected by questionnaire as an instrument to prove the results of the research, to test the hypothesis in this study using path analysis with Smart PLS ver. 3.0. The sampling method used a non-probability sampling method with a purposive sampling technique (100 people). The results of the study indicate that product design has a positive and significant effect on brand image. Product quality has a positive and significant effect on brand image. Competitive pricing has a positive and significant effect on brand image. Product design has a positive and significant influence on purchasing decisions.Product quality has a positive and significant influence on purchasing decisions.Competitive prices have a positive and significant effect on purchasing decisions. Brand image has a positive and significant influence on purchasing decisions. Product design has a positive and significant influence on purchasing decisions through brand image. Product quality has a positive and significant influence on purchasing decisions through brand image.And Competitive prices have a positive and significant influence on purchasing decisions through brand image.